The Public Policy Doctrine in Choice of Law: A Reconsideration of Older Themes - Gary J. Simson (Washington University Law Quarterly, 1974)
The parochialism argument against the public policy doctrine is one which can and should be made. It needs to be formulated, though, not in the metaphysical “right”-“wrong” terms in which Beach and his ideological brethren cast it, but instead contextually, in terms of the aggregate social consequences of the doctrine’s employment. This Article attempts both to supplement and partly to supplant the Paulsen-Sovern contentions against the doctrine by reinvigorating—or, perhaps more precisely, bringing to maturation—arguments directed at the doctrine’s parochial tenor.
Keywords: Conflict of laws; Public policy doctrine; Paulsen-Sovern